Advances in bioremediation of antibiotic pollution in the environment - Gul, Saima; Hussain, Sajjad; Khan, Hammad; Khan, Khurram Imran; Khan, Sabir [UNESP]; Ullah, Sana; Clasen, Barbara (Elsevier, 2021)
Antibiotics are phenomenal compounds that arise in the areas of medicine, agriculture, aquaculture, and animal husbandry. During the last few decades, the prescribed and non-prescribed consumption of antibiotics has increased worldwide. Enormous amounts of antibiotics and their metabolites are released into wastewater because of their incomplete absorption in living bodies. The presence of antibiotics even at nano or microgram levels in aquatic environments poses a substantial risk to human and aquatic organisms. The water pollution due to these products may be worsened by the presence of antibiotic-resistant bacteria and antibiotic-resistant genes. Many conventional water treatment plants are not able to completely eliminate antibiotics, as pollutant removal efficiency depends on their physiochemical properties. Antibiotics may be removed via physicochemical processes, advanced oxidation processes (like adsorption, photolysis, photo-Fenton, ozonation, electrooxidation, and heterogeneous catalysis), and bioremediation based on fungi, algae, or aerobic-anaerobic bacteria to degrade pollutants in waster. In this chapter, we initially discuss contamination of water resources with antibiotic and then elaborate on possible bioremediation strategies. Furthermore, recent advances such as omics approaches, nanotechnological developments, electrokinetics, and coupling of bioremediation with electrochemical processes are discussed with respect to antibiotic degradation. Finally, the future perspectives, scope, and limitations of bioremediation techniques are precisely articulated with a component of hopefulness for researchers working in this field.
Keywords: Antibiotics; Biodegradation; Bioremediation; Contamination; Wastewater